THE IMPACTS OF ONLINE GAME ON THE MORAL OF CHILDREN IN SP 3 PRODE - SUWARNI SUWARNI; IWAN JAZADI; IGA WIDARI (GANEC SWARA, 2023)
The development of the modern era of digitalization has led to some very rapid advances in humans and technology. One of the modern lifestyles today is the use of the internet which is commonly accessed by many people from all over the world regardless of the user’s age limit. This study aims to determine the impacts of online games on children's moral due to frequent playing online games, and to find out the efforts of parents in overcoming inappropriate behavior in children due to the frequent playing of online games in the village of SP 3 Prode Plampang Sub-district Sumbawa Regency. The researchers involved seven children and seven  parents as research informants. This study used a qualitative method. The results of the study show that the presence of online games have positive and negative impacts on children individual moral, social, and religion in SP 3 Prode village.